الأعراض الاكتئابية وعلاقتها بالألكسيثيميا والمخططات المعرفية اللاتكيفية لدى طالبات الجامعة - جريش، إيمان عطية حسين منصور (جامعة الزقازيق - كلية التربية, 2017)
هدفت الدراسة الحالية إلى التعرف على طبيعة العلاقة الارتباطية بين الأعراض الاكتئابية والالكسيثيميا والمخططات المعرفية اللاتكيفية لدى طالبات الجامعة، ومدى الإسهام النسبي لمتغيري الالكسيثيميا والمخططات المعرفية اللاتكيفية بأبعادهما في التنبؤ بالأعراض الاكتئابية لدى طالبات الجامعة، وكذلك التوصل لأفضل نموذج سببي يفسر العلاقة السببية بين الأعراض الاكتئابية والالكسيثيميا والمخططات المعرفية اللاتكيفية لدى طالبات الجامعة، ولقد أجريت هذه الدراسة على عينة قوامها (218) طالبة بكلية التربية الإسماعيلية – جامعة قناة السويس ممن تتراوح أعمارهن بين (18 : 22) سنة بمتوسط عمر (20) سنة، ولقد استجابت الطالبات عينة الدراسة لأدوات الدراسة المتمثلة في : 1-قائمة بيك للاكتئاب (BDI-I) إعداد بيك وستير (Back & Steer, 1993) تعريب أحمد عبد الخالق (1996). 2-مقياس والالكسيثيميا (إعداد الباحثة). 3-مقياس المخططات المعرفية اللاتكيفية إعداد يونج (Young, 2005)، تعريب محمد عبد الرحمن ومحمد سعفان (2014). وبتحليل نتائج الدراسة إحصائياً باستخدام برنامج SPSS وبرنامج الليزر فقد توصلت الدراسة إلى نتائج أهمها: 1-توجد علاقة ارتباطية موجبة دالة إحصائياً بين الأعراض الاكتئابية والالكسيثيميا والمخططات المعرفية اللاتكيفية لدى طالبات الجامعة. 2-عدم إسهام والالكسيثيميا وأبعادها في التنبؤ بالأعراض الاكتئابية لدى طالبات الجامعة. 3-يختلف إسهام المخططات المعرفية اللاتكيفية بمجالاتها في التنبؤ بالأعراض الاكتئابية لدى طالبات الجامعة. 4-لمجال (الانقطاع والرفض) "كأحد مجالات المخططات المعرفية اللاتكيفية" تأثيراً مباشراً موجباً ودالاً إحصائياً على الأعراض الاكتئابية لدى طالبات الجامعة. 5-لمجال (الحذر الزائد والكبت) "كأحد مجالات المخططات المعرفية اللاتكيفية" تأثير مباشر موجب ودال إحصائياً على الالكسيثيميا لدى طالبات الجامعة. 6-تكون متغيرات الدراسة (الأعراض الاكتئابية والالكسيثيميا والمخططات المعرفية اللاتكيفية) فيما بينها نموذجاً يوضح العلاقة السببية بينها.
The present study aims to identify the correlation among depressive symptoms, Alexithymia, and the maladaptive cognitive schemas among university students, and to showto what extent the variables of bothAlexithymia and the maladaptive cognitive schemas relatively contribute to the prediction of the depressive symptoms among the university students. The study also aims to reach a casual model that explains the casual relationship among depressive symptoms, Alexithymia, and the maladaptive cognitive schemas. The study is conducted on a sample that consists of 218 students at the faculty of Education in Ismailia, Suez Canal University. The age of those students range from 18 to 22 years old, with an average age of 20 years. The students are responsive to the tools of the study, which are as follows: 1-Beck’s list of depression (BDI-I), Beck and Steer preparation (Beck & Steer, 1993) and the Arabization of Ahmed Mohamed Abdul Khaliq 2-AIexithymia scale prepared by the researcher. 3-The maladaptive cognitive schemas scale prepared by Young (Young , 2005), and the Arabization of Mohamed Alsayed Abdul Rahman and Mohamed Ahmed Ibrahim Safaan (2014). By analyzing the results of the study using the statistical program SPSS and the laser program, the current study reaches the following findings, the most important of which are: 1-There is a positive statistical correlation among depressive symptoms, Alexithymia, and the maladaptive cognitive schemas among university students. 2-Alexithymia and its dimensions do not contribute in the prediction of depressive symptoms among university students. 3-The contribution of maladaptive cognitive schemas and its areas varies in predicting depressive symptoms among university students. 4-Disconnection and rejection, one of the fields of maladaptive cognitive schemas, have a direct positive and significant statistical effect on the depressive symptoms among university students. 5-Over vigilance and inhibition, as one of the fieldsof maladaptive cognitive schemas, have a direct positive and significant statistical effect on Alexithymia among university students. 6-The variables of the study (depressive symptoms, Alexithymia, and the maladaptive cognitive schemas) are considered as a pattern that shows the casual relationship among them.
Keywords: طلاب الجامعة -- المخططات المعرفية -- الأعراض الاكتئابية -- الألكسيثيميا